2017
DOI: 10.1002/ccr3.910
|View full text |Cite
|
Sign up to set email alerts
|

Conglomeration of Trabecular and Psammomatoid variants of juvenile ossifying fibroma – a rare case report

Abstract: Key Clinical MessageJuvenile ossifying fibroma is an uncommon benign fibro‐osseous lesion occurring in the craniofacial skeleton with a high recurrence rate. It has two distinct histopathologic variants: one trabecular and the other which are exclusive to each other. This case reveals a rare and unique combination of both the patterns in the same lesion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 14 publications
(43 reference statements)
0
2
0
Order By: Relevance
“…A wide distribution of age is noticed in both variants, ranging from 16 to 33 years for psammamatoid and 8.5 to 12 years for trabecular. [ 2 6 7 ] This wide array of age distribution takes the nomenclature of this lesion towards contradiction. The name ‘juvenile’, with its varying demographics, raises a question and an opinion from the author, whether the same nomenclature can be retained for this entity of ossifying fibroma.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A wide distribution of age is noticed in both variants, ranging from 16 to 33 years for psammamatoid and 8.5 to 12 years for trabecular. [ 2 6 7 ] This wide array of age distribution takes the nomenclature of this lesion towards contradiction. The name ‘juvenile’, with its varying demographics, raises a question and an opinion from the author, whether the same nomenclature can be retained for this entity of ossifying fibroma.…”
Section: Discussionmentioning
confidence: 99%
“…A couple of cases with the co-existence of both variants were reported earlier, one in the skull base and the other in the maxilla. [ 2 8 ] The reason for the concurrence of both these entities may be attributed to the cell-rich stroma containing fibroblastic-spindle cells, surrounding osteoblasts and immature cellular osteoid. Since the behaviour of the lesion varies between psammomatoid and trabecular, with trabecular being more aggressive, the behaviour of this dual-type lesion is foreseen to be even more erratic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Those authors hypothesized that the reason may be a cumulative effect of the pathogenesis of the lesion or possibly a collision of 2 separate lesions. 42 A study by Owosho et al demonstrated that although the 2 variants of JOF are determined histologically, it might be possible to distinguish them radiologically. 41 Those authors described PJOF typically appearing as a ground-glass radiopaque structure with a central radiolucent core or as a homogeneous lesion without varying radiodense and radiolucent areas.…”
Section: Discussionmentioning
confidence: 99%
“…Because of the high recurrence rate, some authors have suggested that immediate reconstruction be avoided and only considered after long clinical and radiologic followup. 42 Although recurrence rates are high, no malignant transformation of these lesions has been reported. 39,40…”
Section: Discussionmentioning
confidence: 99%